The Effect of Edamame Sprout Milk on Flavonoid Content and Sensory Properties of Yogurt Enriched with Tumeric and Aromatic Ginger - Hery Winarsi; Friska Citra Agustia; Dilla Ambar Dewi (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2026)
Dyslipidemia is a lipid metabolism disorder characterized by oxidative stress resulting from excessive production of reactive oxygen species, which contributes to the development of cardiovascular diseases. Nevertheless, the consumption of antioxidant-rich foods, such as edamame sprout yogurt enriched with turmeric and aromatic ginger, may help alleviate oxidative stress. This study evaluated the effects of edamame sprout milk and skim milk proportions, turmeric–aromatic ginger extract, and lactic acid bacteria (LAB) on total flavonoid and vitamin C contents, and hedonic sensory properties of edamame sprout–based yogurt enriched with turmeric and aromatic ginger (Estag-Yo). A factorial randomized block design was used. Proportions of edamame sprout milk (Eds-M) to skim milk were 90:10, 80:20, and 70:30; turmeric–aromatic ginger (Tag) extract levels were 5% and 10%; and LAB concentrations were 0.3% and 0.5%, with three replications. Flavonoids were measured using a quercetin standard, vitamin C via iodometric method, and sensory traits using a scoring method. Data were analyzed using ANOVA and DMRT at a 5% significance level. The optimum formula comprised 70% Eds-M, 30% skim milk, 5% Tag extract, and 0.5% LAB. Estag-Yo contained 882.94 mg QE/100 g flavonoids, 57.84 mg/100 g vitamin C, 2.23x109 CFU/mL probiotics, and was well accepted. These findings suggest that edamame sprout yogurt enriched with turmeric and aromatic ginger has the potential to improve antioxidant status and lipid metabolism, thereby supporting the management of dyslipidemia.